2021
DOI: 10.48550/arxiv.2110.14652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence from Disrupted Halo Dwarfs that $r$-process Enrichment via Neutron Star Mergers is Delayed by $\gtrsim500$ Myrs

Rohan P. Naidu,
Alexander P. Ji,
Charlie Conroy
et al.

Abstract: The astrophysical origins of r-process elements remain elusive. Neutron star mergers (NSMs) and special classes of core-collapse supernovae (rCCSNe) are leading candidates. Due to these channels' distinct characteristic timescales (rCCSNe: prompt, NSMs: delayed), measuring r-process enrichment in galaxies of similar mass, but differing star-formation durations might prove informative. Two recently discovered disrupted dwarfs in the Milky Way's stellar halo, Kraken and Gaia-Sausage Enceladus (GSE), afford preci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 100 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…Their chemical evolution modeling supports the former scenario, in agreement with our results, which we discuss in detail in the following section comparing element abundances to Ba. Indeed, a more recent study by Naidu et al (2021) proposed that the r-process enrichment from NSM is delayed by 0.5 to 1 Gyr to explain their GES Eu abundance.…”
Section: [Y/eu] and [Eu/mg]mentioning
confidence: 99%
See 1 more Smart Citation
“…Their chemical evolution modeling supports the former scenario, in agreement with our results, which we discuss in detail in the following section comparing element abundances to Ba. Indeed, a more recent study by Naidu et al (2021) proposed that the r-process enrichment from NSM is delayed by 0.5 to 1 Gyr to explain their GES Eu abundance.…”
Section: [Y/eu] and [Eu/mg]mentioning
confidence: 99%
“…Very recently, there have been works by Matsuno et al (2021), Aguado et al (2021), andNaidu et al (2021) that focus on the r-process in GES stars where all found elevated Eu, highlighting the r-process enhancement in the GES system. There are various sites for r-process production (e.g., electron-capture supernovae or magnetorotationally-driven supernovae, Cescutti & Chiappini (2014)) but the simple chemical evolution model from Matsuno et al (2021) best agree with a neutron star merger scenario (e.g.…”
Section: Comparison To Previous Studies Of Low-𝛼 Starsmentioning
confidence: 99%
“…Measurements of excess [Ba/Fe] and [Eu/Fe] abundances in the dwarf galaxy Reticulum II argue for not only a rare and prolific event, but one capable of enriching the galaxy early in its history (Ji et al 2016a;Tarumi et al 2020), pointing towards a potential rare SN subtype whose r -process production would follow star formation (Côté et al 2019;Siegel et al 2019). Further evidence of heavy r -process enrichment in the disrupted dwarf galaxy Gaia Sausage Enceladus (∼3.6 Gyr star formation duration) but not in the disrupted dwarf galaxy Kraken (with ≈2 Gyr star formation duration) points towards multiple r -process enrichment sites operating on different timescales (Naidu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These astronomical sites have been tested with Galactic chemical evolution models that lead to different conclusions. Recent studies suggest that multiple r-process sites are required to explain the r-process abundances in the Galaxy (e.g., Haynes & Kobayashi 2019;Yamazaki et al 2021;Farouqi et al 2021;Tsujimoto 2021;Naidu et al 2021). Molero et al (2021) argue that the same applies for ultra faint dwarf galaxies.…”
mentioning
confidence: 99%